1992
DOI: 10.1002/ijc.2910520208
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic overlaps between pleomorphic malignant T‐cell lymphomas and mixed‐cellularity Hodgkin's disease

Abstract: Histologically diagnosed, or in part questionable, malignant pleomorphic peripheral T-cell lymphomas (pPTCLs, n = 16) and mixed-cellularity Hodgkin's disease (MCHD, n = 12) were objectively compared by the use of combined immunohistochemistry on paraffin sections, test-point analysis of tissue components, and semi-automated nuclear morphometry on semi-thin resin sections. Classical, qualitative histomorphological distinction of these sub-types of lymphomas proved to be valid and is probably still the best meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…We conclude from these findings that the identification of presumed mitotic or damaged H-RS cells in sections not stained for CD30 can be accepted with greater confidence than anticipated. The percentage of distinct non-neoplastic cell types was close to the values reported previously (Tosi et al, 1992; details not shown).…”
Section: Numerical Comparison Of Cd30+ Cells With Conventionally Idensupporting
confidence: 90%
See 1 more Smart Citation
“…We conclude from these findings that the identification of presumed mitotic or damaged H-RS cells in sections not stained for CD30 can be accepted with greater confidence than anticipated. The percentage of distinct non-neoplastic cell types was close to the values reported previously (Tosi et al, 1992; details not shown).…”
Section: Numerical Comparison Of Cd30+ Cells With Conventionally Idensupporting
confidence: 90%
“…We carried out differential counts in parallel and expressed the proportion of distinct cell types (Tosi et al, 1992) as percentages of all reactive cells. In sections immunostained for CD30 only, all CD30+ cells in 60 randomly chosen HPF (approximately 25,000 cells of all types per case) were registered and the percentages and MI (in %) per case of CD30+ large cells and CD30-small lymphoid cells were established.…”
Section: Cell Countsmentioning
confidence: 99%